(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
Technology is frequently used in a variety of ways by educational systems to make English language classroom lessons enjoyable and meaningful. Digital storytelling (DS) has developed into a useful instructional tool for improving learners’ integrated language skills that can be used in the teaching and learning process for both students and teachers. We conducted a systematic analysis in this paper to validate the research trends of technology enhanced digital storytelling (DS) in education published between 1996 and 2023. In the current study we attempted to gather all Scopus-based 1856 publications for 27 years involving digital storytelling and integrated language skills as keywords. This paper mainly used bibliometric analysis which bibliometric methods are mainly utilized to assess the productivity of scientific outputs quantitatively. This research investigated the most cited articles in DS-related journals, countries, publishing authors, common keywords, research methods, and application domains in the field. The VOSviewer software was used to examine the relationship between keywords in this paper. The scientometric analysis demonstrated that computerized narrating can be utilized as a valuable device by teachers in working on integrated language skills of learners from different degrees of schooling. The majority of these research papers’ authors provided empirical evidence to support the benefits of using digital storytelling in the classroom to improve students’ all four skills.